Building an Outstanding Team: Analyzing HR Strategies for Optimal Performance at PT Al Barik Travel and Umrah Malang - Dharmawan, M. Irfan; Sawitri, Dyah; Hadiyati, Ernani (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes HR strategies for optimal performance at PT Al Barik Travel and Umrah Malang, focusing on building an outstanding team through a SWOT analysis. It identifies key strengths, such as a skilled workforce and strong customer relationships, and pairs them with emerging opportunities in the travel industry, including the growing demand for personalized services and digital solutions. Recommended SO strategies include leveraging skilled employees to explore new markets and enhancing customer experiences through innovative technology. Ultimately, the research concludes that aligning organizational strengths with market opportunities can lead to improved performance and competitive advantage, emphasizing the importance of continuous training and development within the team.